Moderate-to-Vigorous Physical Activity and Body Composition in Children from the Spanish Region of Aragon - Pilar Ferrer-Santos; Iris Iglesia; Borja Muñiz-Pardos; María Luisa Miguel-Berges; Paloma Flores-Barrantes; Luis A. Moreno; Gerardo Rodríguez-Martínez (MDPI AG, 2021)
Most of the studies analyzing the effect of moderate to vigorous physical activity (MVPA) on children's health do not contain information on early stages or do not use accurate methods. We investigated the association between PA and body composition using objective methods, perinatal data, lifestyle behaviors, and World Health Organization (WHO) physical activity (PA) recommendations. The CALINA study is a longitudinal observational cohort study of children born in Aragon (Spain) in 2009. A total of 308 7-year-old children (52.3% boys) were assessed. We used dual-energy X-ray absorptiometry (DXA) and accelerometry. Rapid weight gain until 12 months and lifestyle behaviors were considered as covariates both in the ANCOVA and linear regression models. A higher percentage of boys met the WHO PA recommendations compared to girls (69.6% vs. 40.9%, respectively; p < 0.001). There was a negative association between MVPA and subtotal fat and abdominal fat in both girls and boys. After adjusting for perinatal and lifestyle variables, we found that subtotal body fat, abdominal fat, and fat mass index (FMI) were significantly lower in those classified as active. MVPA was associated with body fat both in boys and girls. More research is needed to identify the cutoffs points of MVPA that generate benefit to boys and girls in all body composition components.